(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2020)
The present paper analyzes some studies that address the Colombian armed conflict of recent decades, from the imaginary and representations of students in basic education, under the assumption that this view allows to identify a little explored field of school dynamics of a phenomenon that takes several decades of validity. To do this, initially, some elements of a historical nature about violence in Colombia are exposed, emphasizing in its periods some of its characteristics: deterritorialization, de-temporalization and desubjectivation; below are some Latin American works that deal with the confluence of ideas of traumatic youth and past, to converge on the objective of this text. In the closing a balance of the incipient existing productivity is made and the importance of harvesting this field of study is indicated given its importance, not only to understand the role of the school in this long journey of the country’s history, but to suggest pedagogical alternatives with a view to the construction of social justice.